Efficacy of carvacrol on Rhipicephalus (Boophilus) microplus engorged female ticks (Canestrini, 1887) (Acari: Ixodidae): effects on mortality and reproduction - Pereira Junior, Amilcar Machado; Camargo-Mathias, M. I. [UNESP]; Daemon, E.; Peconick, A. P.; Lima-Souza, J. R. [UNESP]; Oliveira, P. R. [UNESP]; Braga, A. S.; Lara, L. J.; Remedio, R. N. (Taylor & Francis, 2019)
The activity of carvacrol was evaluated in R. microplus female ticks by estimating the mean lethal concentration (LC 50 ) and the acaricidal efficacy. Ticks were subjected to the Adult Immersion Test (AIT) to calculate LC 50 . From this value, the AIT was performed again at the concentrations of 20%, 40%, 60%, 80% and 100% of the LC 50 . Two control groups were established: one treated with distilled water and one with the solvent (ethanol 50%). The following parameters were evaluated: female weight before oviposition, egg mass weight, pre-oviposition and incubation period, hatching percentage, egg production index, fecundity rate, estimated reproduction, reduction in oviposition and hatching, and product efficacy. The obtained LC 50 was 20.11 mg/mL. Egg mass weight, egg production index, pre-oviposition and fecundity rates of groups treated with 80% and 100% of LC 50 were statistically different when compared to control groups. The product efficacy in groups treated with 100% of LC 50 was 61.10%.
Keywords: cattle; control; LC50; Phytotherapy; ticks